1982
DOI: 10.1577/1548-8659(1982)111<102:eotoga>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Triploidy on Growth and Gonad Development of Channel Catfish

Abstract: Diploid (2n = 58) and triploid (3n = 87) cfiannel catfish Ictalurus punctatus were reared indoors in circular fiberglass tanks equipped with rotating disc biofilters. Triploids were significantly heavier than diploids at 8 months of age and older. Triploid male and fbmale channel catfish also had smaller gonads with altered histology. Triploids converted feed more efficiently, and may provide greater profits in commercial catfish culture than diploids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
4

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 0 publications
4
54
0
4
Order By: Relevance
“…In general, artificially produced triploid fish often possess undeveloped gonads (Purdom 1976;Wolters et al 1982;Benf ey and Sutterlin 1984;Suzuki et al 1985). In this study, it was found that the gonads of triploid ayu were also undeveloped and that both female and male triploids were completely sterile.…”
Section: Discussionmentioning
confidence: 56%
“…In general, artificially produced triploid fish often possess undeveloped gonads (Purdom 1976;Wolters et al 1982;Benf ey and Sutterlin 1984;Suzuki et al 1985). In this study, it was found that the gonads of triploid ayu were also undeveloped and that both female and male triploids were completely sterile.…”
Section: Discussionmentioning
confidence: 56%
“…Sin embargo, de los diferentes métodos el más fácil, barato y efectivo parece ser el choque de temperatura frío o caliente, según la especie que se trate, ya que no requiere el uso de químicos, tampoco de aparatos costosos y puede ser utilizado para tratar una gran cantidad de huevos (Lemoine & Smith, 1980;Arai & Wilkins, 1987;Benfey & Donaldson, 1988;Tiwary et al, 2004;Piferrer et al, 2009;Kizak et al, 2013). El choque en frío ha sido muy efectivo en especies de aguas templadas a cálidas, como es el caso de una gran cantidad de especies explotadas actualmente, como el pez gato de canal, Ictalurus punctatus (Wolters et al, 1982), la carpa herbívora, Ctenopharyngodon idella (Cassani & Caton, 1985), el misgurno chino, Misgurnus mizolepis (Kim et al, 1994), el fletán, Hippoglossus hippoglossus (Holmerfjord & Refstie, 1997), la lubina, Dicentrarchus labrax (Felip et al, 1997), el rodaballo, Scophthalmus maximus (Piferrer et al, 2003) y la cabrilla arenera, Paralabrax maculatofasciatus (Alcántar-Vázquez et al, 2008).…”
Section: Figuraunclassified
“…Fast (1998) menciona que la variación observada en los resultados obtenidos en especies relacionadas, indica que los beneficios potenciales de la triploidía son altamente especie-específicos. La realidad es, que excluyendo a algunas especies de tilapias y bagres (Wolters et al, 1982;Tiwary et al, 1997;Fast, 1998), los organismos triploides raramente crecen más rápido que los organismos diploides en las primeras etapas de cultivo, previas a la maduración sexual. Dunham (2004) menciona que generalmente los organismos diploides crecen más rápido hasta el inicio de la maduración y hasta entonces, los organismos triploides comienzan a crecer más rápido y a tener mejores tasas de conversión alimenticia.…”
Section: Crecimientounclassified
See 2 more Smart Citations